Chemical composition and larvicidal activity of Rollinia leptopetala (Annonaceae) - Feitosa,Edinilza M. A. (2009)
The aim of present study was to describe the chemical composition of the essential oils from the leaf and stem of Rollinia leptopetala R. E. Fries (Annonaceae) and to evaluate the larvicidal activities of these essential oils, of the methanol extract from roots of this plant and of the oxoaporphine alkaloid, liriodenine (1) against the third-instar of Aedes aegypti larvae. The methanol extract from the roots showed larvicidal activity with LC50 64.6 ± 1.5 ppm. Higher activity was observed for the isolated alkaloid liriodenine (1), LC50 3.6 ± 0.4 ppm. The essential oils from the leaves and stems, also exhibited larvicidal activity with LC50 104.7 ± 0.2 and 34.7 ± 0.3 ppm, respectively. These results suggest R. leptopetala as a source of natural larvicidal compounds. This is the first report about the chemical composition and larvicidal activity of the leaf and stem essential oils of R. leptopetala.